Genetic analysis of 50-year old Brazilian pine (Araucaria angustifolia) plantations: Implications for conservation planning - Ferreira D.K. (2012)
In order to determine the implications of including planted populations in conservation planning, we investigate the structure and genetic diversity, mating system, and effective population size within families in three planted and one natural Araucaria angustifolia populations. The study area is a Brazilian National Forest in southern Brazil, established in the 1950s. Genetic analysis was investigated using nine allozyme loci. Significant and positive fixation index was detected for the adults of all studied populations. Although we observed lower levels of genetic diversity and biparental inbreeding in some populations, their pattern of mating, similar to that expected in panmixia, indicates that all populations can be used in conservation planning. Furthermore, the presence of unique alleles and the significant genetic differentiation among all adult populations (F ST = 0.404) reinforces that all populations are important conservation resources. The average paternity correlation was high in almost all populations, showing that open-pollinated families are composed of mixtures of half- and full-sibs. With regards to conservation strategies, our results suggest that seed collection from at least 133 seed trees is necessary to retain a reference effective population size of 500. Our results confirm that the planted Araucaria forests in southern Brazil can be useful as a genetic resource for conservation, breeding and reforestation strategies for this threatened species. © 2011 Springer Science+Business Media B.V.